ENHANCING STUDENTS’ LEARNING OUTCOMES: BITS AND PIECES GAME - Sriati Usman; Budi Budi; Abdul Kamaruddin; Ayu Faradila (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThis research analyzes the implementation of the